Market linkages : Chinese influence on global financial markets - Horniaková, Veronika; Stádník, Bohumil; Janda, Karel; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2017)
Thesis is looking into the current issue of financial market integrations and linkages between them. In recent year, the topic of China has been emerging to the forefront of academic research, therefore the focus of this paper is dedicated to the integration of Chinese market. The goal is to establish whether there exists an interdependency between Chinese and world stock markets and evaluate and analyse potential influence of China on world indices. The theory standing behind financial integration suggests that individual markets are becoming mutually dependant. Chinese efforts to become a part of global economy gradually become successful which creates room for academic research. This paper focuses on stock indices of two Chinese stock markets in relation to American, English, Japanese, German, Dutch and French indices. Cross-correlation analysis, causal analysis and co-integration analysis are applied to individual indices in order to find the results.
Vedoucí práce: Bohumil Stádník
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: bankovnictví a pojišťovnictví [obor dipl. práce]; diplomové práce; master's theses